2008
DOI: 10.1161/strokeaha.108.518175
|View full text |Cite
|
Sign up to set email alerts
|

Unique Cortical Physiology Associated With Ipsilateral Hand Movements and Neuroprosthetic Implications

Abstract: Background and Purpose-Brain computer interfaces (BCIs) offer little direct benefit to patients with hemispheric stroke because current platforms rely on signals derived from the contralateral motor cortex (the same region injured by the stroke). For BCIs to assist hemiparetic patients, the implant must use unaffected cortex ipsilateral to the affected limb. This requires the identification of distinct electrophysiological features from the motor cortex associated with ipsilateral hand movements. Methods-In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 61 publications
4
60
0
1
Order By: Relevance
“…In particular, if a certain part of the brain is not functioning to achieve a functional motor output, as in the case of spastic hemiplegia, in which 1 hemisphere is affected; the use of an alternate cortical location of motor intention may be required. Thus the demonstration of ipsilateral motor movements as a generator of effective control signals by 4 of our pediatric subjects, as has been reported, 14 is particularly exciting.…”
Section: Figurementioning
confidence: 54%
See 1 more Smart Citation
“…In particular, if a certain part of the brain is not functioning to achieve a functional motor output, as in the case of spastic hemiplegia, in which 1 hemisphere is affected; the use of an alternate cortical location of motor intention may be required. Thus the demonstration of ipsilateral motor movements as a generator of effective control signals by 4 of our pediatric subjects, as has been reported, 14 is particularly exciting.…”
Section: Figurementioning
confidence: 54%
“…14,15 The average (with 95% confidence interval [CI]) mean and maximum accuracy during the overt control experiments were calculated for both groups and compared.…”
Section: Figurementioning
confidence: 99%
“…This is of particular importance for BMI applications targeting paresis caused by motor cortex damage, e.g., in stroke. Using a single-trial classification approach, we extended results from previous studies indicating that arm movement kinematics can be reconstructed from ipsilateral cortex [85, 87, 88]. We investigated the relationship between contra- and ipsilateral activity and found that, in some areas, ipsi- and contralateral movement representations are similar enough that classifiers trained on contralateral activations transfer to ipsilateral activations, and vice versa.…”
Section: Brain-computer Interfacesmentioning
confidence: 62%
“…In order to achieve that, we shall rely on a developed brain wave signal detection devices (like the massive signals head cap) for brain waves detection rehabilitation that synthesizes recent developments in neurophysiology, electronics, and physical therapy into a BCI hand orthosis. Such brain waves signals were present in cortex anterior to ipsilateral primary motor cortex, with wave patterns operating below 40Hz [12], [13]. Such patterns are accessible via EEG.…”
Section: A Robotics and Rehabilitationmentioning
confidence: 99%